2016
DOI: 10.1152/ajprenal.00527.2015
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin ameliorates the exaggerated exercise pressor response in patients with chronic kidney disease: a randomized controlled trial

Abstract: Chronic kidney disease (CKD) patients have an exaggerated increase in blood pressure (BP) during rhythmic handgrip exercise (RHG 20%) and static handgrip exercise (SHG 30%). Nitric oxide levels increase during exercise and help prevent excessive hypertension by both increasing vasodilation and reducing sympathetic nerve activity (SNA). Therefore, we hypothesized that tetrahydrobiopterin (BH4), an essential cofactor for nitric oxide synthase, would ameliorate the exaggerated exercise pressor response in CKD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…For example, several studies have shown that the physiologic elevation in heart rate and BP that normally occur during exercise is exaggerated in people with CKD, potentially due to the lower bioavailability of nitrous oxide and the sympathetic nervous system over-activation in this population. [5658] Whether these alterations in endothelial function and neurohormonal systems influence the longer-term training response to exercise in CKD is not known. However, in other conditions associated with endothelial dysfunction, such as cardiovascular disease and diabetes, exercise training has been associated with improvements in endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have shown that the physiologic elevation in heart rate and BP that normally occur during exercise is exaggerated in people with CKD, potentially due to the lower bioavailability of nitrous oxide and the sympathetic nervous system over-activation in this population. [5658] Whether these alterations in endothelial function and neurohormonal systems influence the longer-term training response to exercise in CKD is not known. However, in other conditions associated with endothelial dysfunction, such as cardiovascular disease and diabetes, exercise training has been associated with improvements in endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that oral sapropterin, the pharmaceutical preparation of tetrahydrobiopterin (BH 4 ), increases reflex vasodilation in healthy older adults through NO-dependent mechanisms in the cutaneous microvasculature (43a, 45). Oral BH 4 supplementation has been shown to reduce muscle sympathetic nervous system activity (MSNA) in patients with chronic kidney disease at rest and during hand grip exercise (35,39), suggesting that it may be capable of acting centrally. Although the mechanisms governing SSNA are distinctly different from those of MSNA, evidenced by age-related reductions in SSNA responsiveness (46) but preserved MSNA responsiveness (18) to heat stress, these data (35,39) nevertheless suggest that interventions that increase BH 4 bioavailability may also centrally modulate sympathetic outflow in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Oral BH 4 supplementation has been shown to reduce muscle sympathetic nervous system activity (MSNA) in patients with chronic kidney disease at rest and during hand grip exercise (35,39), suggesting that it may be capable of acting centrally. Although the mechanisms governing SSNA are distinctly different from those of MSNA, evidenced by age-related reductions in SSNA responsiveness (46) but preserved MSNA responsiveness (18) to heat stress, these data (35,39) nevertheless suggest that interventions that increase BH 4 bioavailability may also centrally modulate sympathetic outflow in humans. Collectively, these results suggest that some intervention strategies, such as BH 4 supplementation, may influence both endothelial function and SSNA responses to hyperthermia in healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
“…18 Treatment with a tetrahydrobiopterin precursor reduces the pressor response and increase in sympathetic outflow that occurs in response to hand grip in subjects with chronic kidney disease. 19 Moreover, administration of BH 4 also prevents the development of endothelium dysfunction, vascular inflammation and atherosclerosis induced by disturbed flow. 20, 21 Acute and short-term administration of BH 4 improves endothelial function in humans with rheumatoid arthritis.…”
Section: Nitric Oxide Synthase Uncoupling and Tetrahydrobiopterinmentioning
confidence: 99%